Coated modified high-entropy sodium vanadium phosphate positive electrode material as well as preparation method and application thereof

By coating the modified high-entropy sodium vanadium phosphate positive electrode material, Na3V2(PO4)3 with high-entropy doping and carbon composite of polymetallic elements is used as the core material, and a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) conductive polymer coating is formed on its surface, which solves the conductivity and stability of the sodium vanadium phosphate positive electrode material in sodium ion batteries, and achieves excellent cycling and rate performance.

CN119852374AActive Publication Date: 2025-04-18BEI JING XI BEI DONG LI KE JI YOU XIAN GONG SI

Patent Information

Application Number
CN202510079264.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The existing sodium vanadium phosphate positive electrode material has problems such as poor electronic conductivity, insufficient ion diffusion rate, low stability, and easy dissolution of V metal in sodium ion batteries, which limits its application in long cycle life and high rate performance.

Method used

By coating the modified high-entropy sodium vanadium phosphate positive electrode material, a polymetallic element high-entropy doped and carbon composite Na3V2(PO4)3 is used as the core material, and a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) conductive polymer coating is formed on its surface to improve the electronic conductivity and structural stability of the material.

Benefits of technology

It effectively enhances the ionic conductivity, electronic conductivity and interface stability of the positive electrode material, inhibits the side reaction between the positive electrode and the electrolyte and the dissolution of vanadium metal, and significantly improves the cycling and rate performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852374A_ABST
    Figure CN119852374A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion batteries, in particular to a coated modified high-entropy sodium vanadium phosphate positive electrode material as well as a preparation method and application thereof. The coated modified high-entropy sodium vanadium phosphate positive electrode material comprises a core material and a poly (3, 4-ethylenedioxythiophene): poly (styrene sulfonate) coating layer coated on the surface of the core material, the core material comprises a sodium vanadium phosphate / carbon matrix material and metal elements doped in the sodium vanadium phosphate / carbon matrix material, and the metal elements comprise at least five of Al, Cu, Ru, Ag, Ni, Co, Zn, Ti, Zr, Mg, Mn and Mo elements. The coated modified high-entropy sodium vanadium phosphate positive electrode material provided by the invention can effectively enhance ionic conductivity, electronic conductivity and interface stability of the positive electrode material, can inhibit side reaction between a sodium vanadium phosphate positive electrode and an electrolyte and dissolution of vanadium metal in a circulation process, and has excellent cycle performance and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a coated modified high-entropy sodium vanadium phosphate positive electrode material, and a preparation method and application thereof. Background Art

[0002] With the development of society, energy demand is increasing, and problems such as fossil energy depletion and environmental degradation are becoming increasingly prominent. Therefore, the development and utilization of new wind and solar energy has attracted widespread attention. However, due to the high wind and solar power abandonment rate, in order to rationally and efficiently utilize wind and solar energy, people are paying more and more attention to the development of energy storage technology. Compared with lithium, sodium is abundant, accounting for about 2.64% of the earth's crust reserves, and is widely distributed and cheap. The sodium-ion battery developed using sodium is similar to the lithium-ion battery in working principle, and has more stable electrochemical performance, low-temperature performance and safety. Sodium-ion batteries are expected to become the next generation of cheap and environmentally friendly new energy storage batteries.

[0003] Sodium vanadium phosphate (Na3V2(PO4)3) with NASICON structure has attracted widespread attention for its high ionic conductivity, high operating voltage, excellent thermal stability and safety, and stable three-dimensional skeleton structure. However, sodium vanadium phosphate is reported to have disadvantages such as poor electronic conductivity, insufficient ion diffusion rate, low stability between the positive electrode material and the electrolyte, and easy dissolution of V metal during the cycle, which limits its application in sodium ion batteries with long cycle life and high rate performance. The electrochemical properties of Na3V2(PO4)3 positive electrode materials can be improved by coating and doping. Simple carbon mixing and high-conductivity ion doping can improve its electronic conductivity, while inorganic oxide coating can improve its ionic conductivity and structural stability to a certain extent, improve surface defects, and improve its electrochemical cycle stability. However, the coating layer obtained by existing coating methods has poor structural stability, low ionic and electronic conductivity, and cannot simultaneously improve the electronic conductivity and structural stability of the positive electrode material.

[0004] Therefore, it is of great significance to provide a new coated modified high-entropy sodium vanadium phosphate positive electrode material to solve the above problems. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a coated modified high-entropy sodium vanadium phosphate positive electrode material and a preparation method and application thereof. The coated modified high-entropy sodium vanadium phosphate positive electrode material provided by the present invention can effectively enhance the ionic conductivity, electronic conductivity and interface stability of the positive electrode material, and can inhibit the side reaction between the sodium vanadium phosphate positive electrode and the electrolyte and the dissolution of vanadium metal during the cycle process, and has excellent cycle performance and rate performance.

[0006] In the first aspect, the present invention provides a coated modified high-entropy sodium vanadium phosphate positive electrode material, wherein the coated modified high-entropy sodium vanadium phosphate positive electrode material comprises a core material and a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) coating layer coated on the surface thereof, wherein the core material comprises a sodium vanadium phosphate / carbon matrix material and metal elements doped therein, wherein the metal elements comprise at least five of Al, Cu, Ru, Ag, Ni, Co, Zn, Ti, Zr, Mg, Mn and Mo elements.

[0007] The sodium vanadium phosphate / carbon refers to a composite material of sodium vanadium phosphate and carbon.

[0008] The coated modified high entropy sodium vanadium phosphate positive electrode material provided by the present invention can effectively enhance the ionic conductivity, electronic conductivity and interface stability of the positive electrode material, and can inhibit the side reaction between the sodium vanadium phosphate positive electrode and the electrolyte and the dissolution of vanadium metal during the cycle process, so that the coated modified high entropy sodium vanadium phosphate positive electrode material provided by the present invention has excellent cycle performance and rate performance, specifically:

[0009] The core material in the coated modified high-entropy sodium vanadium phosphate positive electrode material provided by the present invention is Na3V2(PO4)3 doped with multiple metal elements and carbon composite, which can effectively improve the electronic conductivity and structural stability of the sodium vanadium phosphate positive electrode material, thereby effectively improving the electronic conductivity and ion transport capacity of the positive electrode material. The poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) conductive polymer coating layer coated on the surface of the core material has a dense and stable structure, which further improves the electronic conductivity of the positive electrode material while isolating the direct contact between the Na3V2(PO4)3 active positive electrode material and the electrolyte, inhibiting the side reaction between the active substance and the electrolyte, thereby reducing the accumulation of harmful by-products on the surface of the electrode material, reducing the interface resistance between the active substance and the electrolyte, ensuring the efficient transmission of sodium ions at the interface, and being able to inhibit the dissolution of V metal during the cycle process, thereby effectively improving the electrochemical properties of the positive electrode material such as the cycle performance and rate performance, and having broad application prospects.

[0010] As a preferred technical solution of the present invention, taking the total mass of the core material as 100%, the mass content of carbon element therein is 0.01-10%, for example 0.01%, 0.1%, 1%, 2%, 5%, 8%, 10% and the like.

[0011] As a preferred technical solution of the present invention, based on the total mass of the core material as 100%, the content of each metal element is 300-2000ppm, for example, 300ppm, 500ppm, 800ppm, 1000ppm, 1200ppm, 1500ppm, 1800ppm, 2000ppm, etc.

[0012] When the content of carbon element and the content of each metal element in the core material are within the above range, the electronic conductivity and structural stability of the positive electrode material can be more effectively improved, thereby more effectively improving the electronic conductivity and ion transport capacity of the positive electrode material.

[0013] As a preferred technical solution of the present invention, based on the total mass of the coated modified high-entropy sodium vanadium phosphate positive electrode material as 100%, the mass content of the poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) coating layer is 1-7%, for example, 1%, 2%, 4%, 6%, 7%, etc.

[0014] When the content of the poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) conductive polymer coating layer is within the above range, the coating layer structure is stable and dense, and at the same time, it can more effectively inhibit the side reaction between the sodium vanadium phosphate positive electrode and the electrolyte and the dissolution of vanadium metal during the cycle process, thereby more effectively improving the cycle performance and rate performance of the positive electrode material.

[0015] In a second aspect, the present invention provides a method for preparing the coated modified high entropy sodium vanadium phosphate positive electrode material according to the first aspect, the preparation method comprising:

[0016] (1) dissolving a vanadium source, a sodium source, a phosphorus source, a metal source, a carbon source and a reducing agent in a first solvent, performing sand milling, drying and sintering to obtain a core material;

[0017] (2) The core material and poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) are mixed with an organic solvent, and after solid-liquid separation and drying, the coated modified high-entropy sodium vanadium phosphate positive electrode material is obtained.

[0018] The preparation method provided by the invention has simple process, the obtained coating layer is evenly distributed, and has strong versatility, which is helpful to promote the industrialization and application of vanadium-based sodium ion battery positive electrode materials.

[0019] As a preferred technical solution of the present invention, the molar ratio of the vanadium element, sodium element and phosphorus element in the vanadium source, sodium source and phosphorus source to the reducing agent is 2:3:3:(0.5-4), for example, 2:3:3:0.5, 2:3:3:1, 2:3:3:2, 2:3:3:3, 2:3:3:4, etc.

[0020] As a preferred technical solution of the present invention, the vanadium source includes any one or more of ammonium metavanadate (NH4VO3), vanadium trioxide (V2O3) and vanadium pentoxide (V2O5).

[0021] As a preferred technical solution of the present invention, the sodium source includes any one or more of sodium acetate (CH3COONa), sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), sodium dihydrogen phosphate (NaH2PO4) and disodium hydrogen phosphate (Na2HPO4).

[0022] As a preferred technical solution of the present invention, the phosphorus source includes any one or more of sodium dihydrogen phosphate (NaH2PO4), disodium hydrogen phosphate (Na2HPO4), ammonium dihydrogen phosphate (NH4H2PO4) and diammonium hydrogen phosphate ((NH4)2HPO4).

[0023] As a preferred technical solution of the present invention, the metal source is any one or more of nitrates, acetates or oxides corresponding to each metal element.

[0024] As a preferred technical solution of the present invention, the carbon source includes an organic carbon source and / or an inorganic carbon source. Preferably, the carbon source includes glucose (C6H 12 O6), sucrose (C 12 H 22 O 11 ), any one or more of carbon nanotubes and graphene.

[0025] As a preferred technical solution of the present invention, the reducing agent is oxalic acid.

[0026] As a preferred technical solution of the present invention, the first solvent includes deionized water.

[0027] As a preferred technical solution of the present invention, the organic solvent includes N-methylpyrrolidone.

[0028] As a preferred technical solution of the present invention, the sanding time in step (1) is 2-6 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, etc.

[0029] As a preferred technical solution of the present invention, the drying in step (1) is spray drying, the inlet air temperature is 180-250°C, for example, 180°C, 200°C, 220°C, 240°C, 250°C, etc., and the outlet air temperature is 80-110°C, for example, 80°C, 90°C, 100°C, 110°C, etc.

[0030] As a preferred technical solution of the present invention, the sintering in step (1) is carried out under an inert gas atmosphere, and the inert gas can be nitrogen or argon.

[0031] As a preferred technical solution of the present invention, the sintering temperature is 600-750°C, for example, 600°C, 650°C, 700°C, 750°C, etc., and the sintering time is 5-12h, for example, 5h, 8h, 10h, 12h, etc.

[0032] When the sintering temperature and time are within the above ranges, the carbon source can be carbonized at high temperature to form a carbon-composite high-entropy doped sodium vanadium phosphate core material with a more stable structure.

[0033] As a preferred technical solution of the present invention, the mixing temperature in step (2) is 40-80°C, such as 40°C, 50°C, 60°C, 70°C, 80°C, etc., and the mixing time is 3-6h, such as 3h, 4h, 5h, 6h, etc. When the mixing temperature and time are within the above ranges, a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) conductive polymer coating layer with a more stable and dense structure can be formed on the surface of the core material.

[0034] As a preferred technical solution of the present invention, the drying in step (2) is vacuum drying, the vacuum drying temperature is 80-150°C, for example 80°C, 100°C, 120°C, 140°C, 150°C, etc., and the vacuum drying time is 6-24h, for example 6h, 9h, 12h, 15h, 18h, 21h, 24h, etc.

[0035] In a third aspect, the present invention provides a positive electrode plate, which includes the coated modified high entropy sodium vanadium phosphate positive electrode material described in the first aspect or the coated modified high entropy sodium vanadium phosphate positive electrode material prepared by the preparation method described in the second aspect.

[0036] In a fourth aspect, the present invention provides a sodium ion battery, comprising the positive electrode sheet described in the third aspect.

[0037] The technical solution provided by the embodiment of the present invention has the following advantages compared with the prior art:

[0038] The coated modified high-entropy sodium vanadium phosphate positive electrode material provided by the present invention can effectively enhance the ionic conductivity, electronic conductivity and interface stability of the positive electrode material, and can also inhibit the side reaction between the sodium vanadium phosphate positive electrode and the electrolyte and the dissolution of vanadium metal during the cycle, and has excellent cycle performance and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0041] Figure 1 This is the XRD pattern of the coated modified high entropy sodium vanadium phosphate positive electrode material prepared in Example 1 of the present invention;

[0042] Figure 2 This is a SEM image of the coated modified high entropy sodium vanadium phosphate positive electrode material prepared in Example 1 of the present invention;

[0043] Figure 3 The first charge and discharge curve of a button cell assembled using the coated modified high entropy sodium vanadium phosphate positive electrode material prepared in Example 1 of the present invention at a rate of 0.1C;

[0044] Figure 4 This is a cycle performance diagram of a button cell assembled using the coated modified high entropy sodium vanadium phosphate positive electrode material prepared in Example 1 of the present invention at a 1C rate;

[0045] Figure 5 This is a rate performance diagram of a button cell assembled using the coated modified high entropy sodium vanadium phosphate positive electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0046] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0047] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0048] Example 1

[0049] This embodiment provides a coated modified high entropy sodium vanadium phosphate positive electrode material and a preparation method thereof, the preparation method comprising the following steps:

[0050] (1) 2 mol of ammonium metavanadate (NH4VO3), 3.0 mol of sodium acetate (CH3COONa), 3 mol of diammonium phosphate (NH4H2PO4), 1 mol of oxalic acid (H2C2O4) and glucose (C6H 12O6) are dissolved in deionized water and mixed, and aluminum oxide, titanium oxide, copper nitrate, ruthenium nitrate and zinc oxide are weighed and added into the above deionized water for mixing according to the contents of aluminum, titanium, copper, ruthenium and zinc in the core material of 1200ppm, 1300ppm, 1100ppm, 1000ppm and 1200ppm respectively, wherein the mass of glucose is added according to the carbon composite amount in the core material accounting for 3wt%, the fully mixed material is sand milled for 4.0h, and then spray dried, the inlet air temperature of the spray drying is 220℃, the outlet air temperature is 100℃, and the spray dried material is sintered at 700℃ for 7h in nitrogen protective gas to obtain the core material;

[0051] (2) Dispersing poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) in N-methylpyrrolidone (NMP), and then adding the core material, the mass of PEDOT:PSS is added according to its content in the final product sample of 2wt%, stirring the above mixture at 60°C for 4h, centrifuging and filtering, and vacuum drying at 100°C for 20h to obtain the coated modified high entropy sodium vanadium phosphate positive electrode material.

[0052] Example 2

[0053] This embodiment provides a coated modified high entropy sodium vanadium phosphate positive electrode material and a preparation method thereof, the preparation method comprising the following steps:

[0054] (1) 1 mol of vanadium pentoxide (V2O5), 1.5 mol of sodium carbonate (Na2CO3), 3 mol of diammonium hydrogen phosphate ((NH4)2HPO4), 2 mol of oxalic acid (H2C2O4) and sucrose (C 12 H 22 O 11 ) are dissolved in deionized water and mixed, and molybdenum dioxide, manganese dioxide, nickel acetate, titanium oxide and zirconium acetate are weighed and added into the above deionized water for mixing according to the contents of molybdenum, manganese, nickel, titanium and zirconium in the core material of 800ppm, 600ppm, 800ppm, 1000ppm and 900ppm respectively, wherein the mass of sucrose is added according to the carbon composite amount in the core material accounting for 5wt%, the fully mixed material is sand milled for 5h, and then spray dried, the inlet air temperature of the spray drying is 200℃, the outlet air temperature is 90℃, and the spray dried material is sintered at 750℃ for 5h in nitrogen protective gas to obtain the core material;

[0055] (2) Dispersing poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) in N-methylpyrrolidone (NMP), and then adding the core material, the mass of PEDOT:PSS is added according to its content in the final product sample of 3wt%, stirring the above mixture at 50°C for 5.5h, centrifuging and filtering, and vacuum drying at 90°C for 22h to obtain the coated modified high entropy sodium vanadium phosphate positive electrode material.

[0056] Example 3

[0057] This embodiment provides a coated modified high entropy sodium vanadium phosphate positive electrode material and a preparation method thereof, the preparation method comprising the following steps:

[0058] (1) 1 mol of vanadium trioxide (V2O3), 3 mol of sodium dihydrogen phosphate (NaH2PO4), 1.5 mol of oxalic acid (H2C2O4) and carbon nanotubes are dissolved in deionized water and mixed. Copper oxide, titanium oxide, cobalt oxide, zirconium oxide and nickel nitrate are weighed and added into the deionized water according to the contents of copper, titanium, cobalt, zirconium and nickel in the core material of 700 ppm, 700 ppm, 500 ppm, 600 ppm and 600 ppm respectively, and mixed. The mass of carbon nanotubes is added according to the carbon composite amount in the core material accounting for 1 wt%. The fully mixed material is sand milled for 3 h and then spray dried. The inlet air temperature of the spray drying is 240° C. and the outlet air temperature is 105° C. The spray dried material is sintered at 600° C. for 10 h in nitrogen protective gas to obtain the core material.

[0059] (2) Dispersing poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) in N-methylpyrrolidone (NMP), and then adding the core material, the mass of PEDOT:PSS being added according to its content in the final product sample being 5wt%; stirring the above mixture at 75°C for 3h, centrifuging and filtering, and vacuum drying at 140°C for 10h to obtain the coated modified high entropy sodium vanadium phosphate positive electrode material.

[0060] Example 4

[0061] This embodiment provides a coated modified high entropy sodium vanadium phosphate positive electrode material and a preparation method thereof, the preparation method comprising the following steps:

[0062] (1) 2 mol of ammonium metavanadate (NH4VO3), 3 mol of sodium bicarbonate (NaHCO3), 3 mol of diammonium hydrogen phosphate ((NH4)2HPO4), 3 mol of oxalic acid (H2C2O4) and graphene are dissolved in deionized water and mixed, and silver nitrate, titanium oxide, zinc oxide, ruthenium nitrate and molybdenum dioxide are weighed and added into the deionized water according to the contents of silver, titanium, zinc, ruthenium and molybdenum in the core material of 1700 ppm, 1500 ppm, 1900 ppm, 1800 ppm and 1600 ppm respectively, wherein the mass of graphene is added according to the carbon composite amount in the core material accounting for 8 wt%. The fully mixed material is sand milled for 5.5 h and then spray dried. The inlet air temperature of the spray drying is 230° C. and the outlet air temperature is 100° C. The spray dried material is sintered at 650° C. for 8 h in nitrogen protective gas to obtain the core material;

[0063] (2) Dispersing poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) in N-methylpyrrolidone (NMP), and then adding the core material, the mass of PEDOT:PSS being added according to its content in the final product sample being 1.5wt%; stirring the above mixture at 45°C for 6h, centrifuging and filtering, and vacuum drying at 120°C for 15h to obtain the coated modified high entropy sodium vanadium phosphate positive electrode material.

[0064] Example 5

[0065] This embodiment provides a coated modified high entropy sodium vanadium phosphate positive electrode material and a preparation method thereof, the preparation method comprising the following steps:

[0066] (1) 1 mol of vanadium pentoxide (V2O5), 3 mol of sodium bicarbonate (NaHCO3), 3 mol of ammonium dihydrogen phosphate (NH4H2PO4), 4 mol of oxalic acid (H2C2O4) and glucose (C6H 12 O6) are dissolved in deionized water and mixed, and magnesium oxide, manganese tetraoxide, cobalt nitrate, zinc oxide and silver nitrate are weighed and added into the above deionized water for mixing according to the contents of magnesium, manganese, cobalt, zinc and silver in the core material of 500ppm, 400ppm, 400ppm, 350ppm and 350ppm respectively, wherein the mass of glucose is calculated as 9.5wt% of the carbon composite amount in the core material, and the fully mixed material is sand milled for 2.5h and then spray dried, the inlet air temperature of the spray drying is 185℃, and the outlet air temperature is 85℃, and the spray dried material is sintered at 725℃ in nitrogen protective gas for 10h to obtain the core material;

[0067] (2) Dispersing poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) in N-methylpyrrolidone (NMP), and then adding the core material, the mass of PEDOT:PSS being added according to its content in the final product sample being 6wt%; stirring the above mixture at 70°C for 5h, centrifuging and filtering, and vacuum drying at 130°C for 8h to obtain the coated modified high entropy sodium vanadium phosphate positive electrode material.

[0068] Comparative Example 1

[0069] This comparative example provides a coated modified sodium vanadium phosphate positive electrode material and a preparation method thereof. The preparation method is the same as that of Example 1, and the difference from Example 1 is that no metal source is added in step (1) of this comparative example.

[0070] Comparative Example 2

[0071] This comparative example provides a high entropy sodium vanadium phosphate positive electrode material and a preparation method thereof. The preparation method is the same as that of Example 1. The difference from Example 1 is that after obtaining the core material, the coating step of step (2) is not performed in this comparative example.

[0072] Comparative Example 3

[0073] This comparative example provides a coated modified high entropy sodium vanadium phosphate positive electrode material and a preparation method thereof. The preparation method is the same as that in Example 1, and the difference from Example 1 is that in this comparative example, the poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) in step (2) is replaced by polyaniline.

[0074] Performance Test 1

[0075] 1. Perform XRD test on the coated modified high entropy sodium vanadium phosphate positive electrode material prepared in Example 1. The XRD pattern of the coated modified high entropy sodium vanadium phosphate positive electrode material prepared in Example 1 is as follows: Figure 1 shown.

[0076] 2. The SEM test was performed on the coated modified high entropy sodium vanadium phosphate positive electrode material prepared in Example 1. The SEM image of the coated modified high entropy sodium vanadium phosphate positive electrode material prepared in Example 1 is as follows: Figure 2 shown.

[0077] Performance Test 2

[0078] The positive electrode materials prepared in the examples and comparative examples were used as positive electrode active materials to prepare positive electrode sheets and assemble button cells.

[0079] The positive electrode materials prepared in the embodiment and the comparative example were respectively used as positive electrode active materials, mixed with SuperP conductive carbon and polyvinylidene fluoride (PVDF) at a ratio of 8:1:1 to obtain positive electrode active slurry, which was then coated on an aluminum foil current collector to prepare a positive electrode sheet. The active material surface density was 5 mg / cm 2 The button cell was assembled in a glove box with high-purity argon atmosphere, using a metal sodium sheet as the counter electrode, 5 Vol% fluoroethylene carbonate added to a 1 M NaClO4 / propylene carbonate solution as the electrolyte, and glass fiber as the separator.

[0080] The electrochemical performance of the assembled button cell was tested, and the voltage window was 2.2 to 3.8V.

[0081] The theoretical capacity of the positive electrode material prepared in the embodiment is calculated as 117 mAh / g. The test results are as follows: Figure 3-5 As shown in Table 1, Figure 3 The first charge and discharge curve of a button cell assembled using the coated modified high entropy sodium vanadium phosphate positive electrode material prepared in Example 1 at a rate of 0.1C; Figure 4 This is a cycle performance diagram of a button cell assembled using the coated modified high entropy sodium vanadium phosphate positive electrode material prepared in Example 1 at a 1C rate; Figure 5 This is a rate performance diagram of a button cell assembled using the coated modified high entropy sodium vanadium phosphate positive electrode material prepared in Example 1.

[0082] The results in Table 1 are as follows:

[0083] Table 1

[0084]

[0085] From Table 1 and Figure 3-5 It can be found that the button battery assembled using the coated modified high-entropy sodium vanadium phosphate positive electrode material prepared by the present invention has excellent rate performance and cycle performance.

[0086] From the comparison between Example 1 and Comparative Examples 1-3, it can be found that high entropy doping and high conductive polymer coating can effectively enhance the ionic conductivity, electronic conductivity and interface stability of the positive electrode material, can inhibit the side reaction between the sodium vanadium phosphate positive electrode and the electrolyte and the dissolution of vanadium metal during the cycle, and effectively improve the cycle stability and rate performance of the positive electrode material.

[0087] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0088] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments described herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A coated modified high entropy sodium vanadium phosphate positive electrode material, characterized in that: The coated modified high-entropy sodium vanadium phosphate positive electrode material includes a core material and a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) coating layer coated on the surface thereof, wherein the core material includes a sodium vanadium phosphate / carbon matrix material and metal elements doped therein, wherein the metal elements include at least five of Al, Cu, Ru, Ag, Ni, Co, Zn, Ti, Zr, Mg, Mn and Mo elements.

2. The coated modified high entropy sodium vanadium phosphate positive electrode material according to claim 1, characterized in that: Taking the total mass of the core material as 100%, the mass content of carbon element therein is 0.01-10%; And / or, based on the total mass of the core material being 100%, the content of each metal element is 300-2000 ppm.

3. The coated modified high entropy sodium vanadium phosphate positive electrode material according to claim 1 or 2, characterized in that: Taking the total mass of the coated modified high entropy sodium vanadium phosphate positive electrode material as 100%, the mass content of the poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) coating layer is 1-7%.

4. The method for preparing the coated modified high entropy sodium vanadium phosphate positive electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: (1) dissolving a vanadium source, a sodium source, a phosphorus source, a metal source, a carbon source and a reducing agent in a first solvent, performing sand milling, drying and sintering to obtain a core material; (2) The core material and poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) are mixed with an organic solvent, and after solid-liquid separation and drying, the coated modified high-entropy sodium vanadium phosphate positive electrode material is obtained.

5. The preparation method according to claim 4, characterized in that: The molar ratio of the vanadium element, the sodium element and the phosphorus element in the vanadium source, the sodium source and the phosphorus source to the reducing agent is 2:3:3:(0.5-4).

6. The preparation method according to claim 4 or 5, characterized in that: The vanadium source includes any one or more of ammonium metavanadate, vanadium trioxide and vanadium pentoxide; And / or, the sodium source includes any one or more of sodium acetate, sodium carbonate, sodium bicarbonate, sodium dihydrogen phosphate and disodium hydrogen phosphate; and / or, the phosphorus source includes any one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate and diammonium hydrogen phosphate; And / or, the metal source is any one or more of nitrates, acetates or oxides corresponding to each metal element; And / or, the carbon source includes any one or more of glucose, sucrose, carbon nanotubes and graphene; And / or, the reducing agent is oxalic acid; and / or, the first solvent comprises deionized water; And / or, the organic solvent comprises N-methylpyrrolidone.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The sanding time in step (1) is 2-6 hours; And / or, the drying in step (1) is spray drying, with an air inlet temperature of 180-250° C. and an air outlet temperature of 80-110° C.; And / or, the sintering in step (1) is carried out in an inert gas atmosphere, the sintering temperature is 600-750° C., and the sintering time is 5-12 hours.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The mixing temperature in step (2) is 40-80° C. and the mixing time is 3-6 hours; And / or, the drying in step (2) is vacuum drying, the vacuum drying temperature is 80-150° C., and the vacuum drying time is 6-24 h.

9. A positive electrode sheet, characterized in that: The positive electrode plate comprises the coated modified high entropy sodium vanadium phosphate positive electrode material according to any one of claims 1 to 3 or the coated modified high entropy sodium vanadium phosphate positive electrode material prepared by the preparation method according to any one of claims 4 to 8.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Preparation method of Li3V2(PO4)3 nanocrystalline / conductive polymer lithium ion battery cathode material

    CN108539133A

  • High-entropy metal phosphate with NASICON structure as well as preparation method and application of high-entropy metal phosphate

    CN114715869A

  • High-entropy polyanionic sodium ion battery positive electrode material and preparation method thereof

    CN116666608A

  • High-entropy doped sodium vanadium fluorophosphate positive electrode material and preparation method thereof

    CN117012918A

  • High-entropy polyanion positive electrode material and preparation method and application thereof

    CN117894976A

Cited By

  • Modified sodium vanadium phosphate positive electrode material as well as preparation method and application thereof

    CN121687907A